Opinion 2477: Hybosorus illigeri Reiche, 1853 (Insecta, Coleoptera): name conserved - ICZN (Bulletin of Zoological Nomenclature, 2021)
The International Commission on Zoological Nomenclature has conserved current usage of the specific name of Hybosorus illigeri Reiche, 1853, a widespread species of scarabaeid beetle, by giving it precedence over the specific names of Hybosorus pinguis Westwood, 1845, Hybosorus roei Westwood, 1845 and Hybosorus carolinus LeConte, 1847.
Keywords: Nomenclature; taxonomy; Coleoptera; HYBOSORIDAE; Hybosorus illigeri; Hybosorus pinguis; Hybosorus roei; Hybosorus carolinus